Ես եմ հացն կենդանի. Քրիստոսի դիմապատկերը հայկական ավանդական լավաշի վրա - Հռիփսիմե Վարդանյան (ՀՀ ԳԱԱ հրատ.)
Статья представляет эксклюзивные образцы народного искусства и повествует об истории возникновения экспонатов (армянские традиционные лаваши с ликом Христа).The article presents exclusive examples of folk art and tells the story of the appearance of exhibits (Armenian traditional lavash with the face of Christ).
Keywords: Philosophy; Psychology; Religion; Christianity